Integrating Local Wisdom and Global Knowledge to Develop Culturally Responsive Education Models - Sophia Anne Milleer (Nusantara Education, 2026)
This study aims to formulate a culturally responsive education model by integrating local wisdom and global knowledge to address the challenge of aligning global educational standards with diverse cultural contexts. In an era marked by rapid globalization and digital transformation, education systems are often pressured to adopt universal frameworks that risk marginalizing indigenous knowledge and local values. This research seeks to bridge this gap by developing a model that is both globally relevant and locally grounded. The study employs a qualitative field research design to examine culturally responsive education in practice. Data were collected through interviews, observations, and documentation involving educators and relevant stakeholders selected purposively. The data were analyzed using thematic analysis to identify key patterns and best practices. Validity was ensured through data triangulation and iterative analysis.  The findings indicate that an effective integration of local wisdom and global knowledge can be achieved through three interconnected components: culturally embedded curriculum design, inclusive and participatory pedagogy, and flexible institutional governance. Culturally embedded curricula incorporate local traditions, values, and epistemologies into global competency frameworks. Inclusive pedagogy emphasizes student-centered learning, community involvement, and culturally sensitive teaching methods. Meanwhile, flexible governance structures enable adaptive policy implementation that aligns educational objectives with both local needs and international benchmarks. This study contributes to the academic discourse by offering an integrative conceptual model that reconciles the dichotomy between global standardization and cultural specificity in education. It provides practical insights for educators, policymakers, and curriculum developers to design more inclusive and contextually relevant learning environments. Additionally, this research lays the groundwork for future empirical studies to validate and refine the proposed model across different cultural and educational settings.